Modern hybrid coloring algorithm - Fabrício Filho, João (2016)
In 1999, Philippe Galinier and Jin-Kao Hao developed the widely praised Hybrid Coloring Algorithm (HCA) to solve the Graph Coloring Problem (GCP), which is a complex computational problem that focuses in coloring all vertices of a given graph with a minimum number of colors, with the constraint that adjacent vertices can not receive the same color. Since then, powerful computer infrastructures have emerged, with considerable benefits to software developers and applications. Thus, the objective of this paper is to analyze in detail the current HCA and propose a modern version with improvements that take advantage of recent computer infrastructures. The expected contribution at the conclusion of this work is to encourage developers to take advantage of modern architectures to solve complex computational problems.